Architecture and death: the shower as device - de Gispert Hernandez, Jordi; Amann y Alcocer, Atxu (Estoa. Journal of the Faculty of Architecture and Urbanism, 2018)
The shower takes an important position within enclosing architecture. As a system, it is spread in penitentiaries in two forms, the gas chamber and the collective shower, becoming an architectonic device where domination is justified as a moral value. The technology process occurs in three stages: in the 18th and 19th centuries, chemical engineering development allows the way to create artificial precise substances, as well as discovering the pharmakon properties of carbonated gas; through the 19th and the 20th centuries, the prison turns from the domestic model to the panoptic form, while pretending to remove suffer in the process of death penalty, using gas chambers; finally, in the First World War the first massive gas attacks take place, and in the Second World War, the gas chamber and the collective showers get together in a single project, the nazi gas chamber.